Kuturani: Creating technology as part of the musical work (REVISTA NODO, 2025)
This article presents a technological augmentation system for acoustic instruments and discusses, from a theoretical perspective, the role of new technologies within musical works and how they can redefine the boundaries of what we consider to be the musical work. We present a quick overview of the development of augmented instruments as part of the creative processes and propose an ontological model that helps placing technology and its development as part of the musical work. We present a characterisation of our low-cost augmentation system, which is adaptable to user requirements, either to facilitate its construction or to adapt to the creative needs of a work. We present the challenges and solutions encountered during the design and construction of this device, and discuss the potential that comes from developing an open system. Finally, we present our reflections on the potential future of the project.